Beyond the core: Do ethnic parties 'reach out' in power-sharing systems?. (August 2021) - Murtagh, Cera; McCulloch, Allison
While power-sharing arrangements are often commended for establishing peaceful relations between major ethnic groups, they are also criticised for excluding 'Others'. Nevertheless, more complex forms of party competition can emerge in power-sharing systems, including parties representing the dominant communities ('ethnic parties') seeking to engage Others ('non-dominant' groups). Drawing on semi-structured interviews with parties from Northern Ireland, we examine the extent to which dominant parties reach beyond their core ethnic constituencies, how and why. We consider increasingly salient non-sectarian issues, such as marriage equality and abortion, and explore how ethnic parties have sought to respond to these debates. We consider whether liberal forms of power-sharing influence the willingness of dominant parties to advance inclusion of non-dominant groups. Our findings suggest that under favourable conditions, flexible power-sharing can create space for incremental moves by ethnic parties to reach out to constituencies beyond their core, gradually moving the system towards more inclusive representation.